2018 AIAA SPACE and Astronautics Forum and Exposition 2018
DOI: 10.2514/6.2018-5364
|View full text |Cite
|
Sign up to set email alerts
|

In-Space Manufacturing at NASA Marshall Space Flight Center: A Portfolio of Fabrication and Recycling Technology Development for the International Space Station

Abstract: The in-space manufacturing project at NASA Marshall Space Flight Center seeks to mature the manufacturing capabilities which will be needed on long duration, long endurance human spaceflight missions. The ability to manufacture materials and parts in space rather than launching them from earth has the potential to reduce logistics requirements and enhance crew safety. The International Space Station serves as a unique orbiting test bed for in-space manufacturing technology development for NASA and its commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…At present, for long-endurance spaceflight missions to planets or asteroids within the solar system, pre-fabricated parts for the mission must be launched from the ground into orbit, which means only limited payload volume fractions are possible and considerable geometric restraints for the payload structure need to be met due to dimensional restrictions onboard ascent vehicles [204]. For long-duration missions, the capacity of manufacturing components to be on-demand provides increased self-sufficiency and increases safety in the process [205]. Aside from long-duration spaceflight missions, recent publications have contended that ISM might also be utilized in the construction of nanosatellites and antenna parts, as well as for repairs of structural satellite components [204].…”
Section: Discussionmentioning
confidence: 99%
“…At present, for long-endurance spaceflight missions to planets or asteroids within the solar system, pre-fabricated parts for the mission must be launched from the ground into orbit, which means only limited payload volume fractions are possible and considerable geometric restraints for the payload structure need to be met due to dimensional restrictions onboard ascent vehicles [204]. For long-duration missions, the capacity of manufacturing components to be on-demand provides increased self-sufficiency and increases safety in the process [205]. Aside from long-duration spaceflight missions, recent publications have contended that ISM might also be utilized in the construction of nanosatellites and antenna parts, as well as for repairs of structural satellite components [204].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that the thermal stress and consequent warpage, delamination, etc., in FFF can be even more problematic on the Moon, particularly when printing big objects or structural components. Thus, FFF on the Moon is more suitable for printing small or functional components, such as oxygen generation adapter, antenna feedhorn [2], personalized pharmaceutical dosage form with tailored performance [28,29], etc.…”
Section: Simulating Fff On the Moonmentioning
confidence: 99%
“…These attributes magnify their indispensability when tradi-tional manufacturing techniques and materials are limited or not immediately available on the Moon. Fused filament fabrication (FFF), one of the material extrusion based AM techniques, is even more promising for long-duration missions: the thermoplastic materials in use can be recycled [1,2], which further reduces the material consumption and logistic cost, and hence promotes the self-sustainability of the process. But, can FFF succeed on the Moon in the first place?…”
Section: Introductionmentioning
confidence: 99%
“…Prater et al has conducted a series of studies with NASA on the ISS to evaluate outcomes of 3D printing of tools in space. [10,18,19] As part of Phase I ISS Results, the FDM printer (Made in Space, ABS) printed 21 parts on the ISS which were examined to evaluate whether material and mechanical performance of ADM was different between earth and low-earth gravity ADM printers. [18] Initial findings from various mechanical and scanning electron microscopy optical testing indicated that some mechanical property differences were detected in low-earth orbit specimens, albeit limited by the number of parts tested.…”
Section: Low-earth Gravity Settingsmentioning
confidence: 99%
“…Results are currently pending, with delivery of the project part of SBIR II-proof of concept study-and exploring manufacture of surgical tweezers, among other tools and applications in space. [19]…”
Section: Low-earth Gravity Settingsmentioning
confidence: 99%